PEMBELAJARAN DARING DI TENGAH WABAH COVID-19 - Bueti, A. (Jurnal Ilmiah Pendidikan dan Keislaman, 2021)
The Covid-19 pandemic has disrupted the conventional learning process. So a solution is needed to answer this problem. Online learning is one alternative that can overcome this problem. The purpose of the study was to obtain an overview of the implementation of online learning in the Islamic Education Study Program of STAI Assalamiyah as an effort to suppress the spread of covid-19 in universities. The research subjects are students of Biology Education Study Program. Data was collected by interview via zoom cloud meeting. Data analysis was performed using Miles & Huberman's interactive analysis technique. The results showed that: (1) students already had the basic facilities needed to take part in online learning; (2) online learning has flexibility in its implementation and is able to encourage the emergence of independent learning and motivation to be more active in learning; and (3) distance learning encourages the emergence of social distancing behavior and minimizes the emergence of student crowds so that they are considered to reduce the potential for the spread of Covid-19 in the university environment. Weak supervision of students, lack of strong signal in remote areas, and high quota fees are challenges in online learning. Increasing learning independence, interest and motivation, the courage to express ideas and questions are other advantages of online learning